2018
DOI: 10.1097/qai.0000000000001718
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Exposure in an HIV-Infected Cohort in Ghana

Abstract: Objective To determine the prevalence and epidemiologic associations of Zika Virus (ZIKV) in HIV-infected patients in Ghana, West Africa. Methods We examined the seroprevalence of ZIKV in HIV/HBV co-infected persons in Ghana from sera samples collected from 2012 to 2014 using ELISA assays and plaque reduction neutralization tests (PRNT). Results Overall, ZIKV antibody was detected in 12.9% of 236 tested samples, though the true estimate of exposure is probably less due cross-reactions with other related vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…A lack of thorough surveillance, together with myriad co-circulating pathogens causing febrile illnesses, make understanding both the past and current prevalence of gestational ZIKV infection and any resulting fetal outcomes in Africa challenging [4042]. Recent seroprevalence studies have now identified low, but consistent circulation of ZIKV in several African [4346] and southeast Asian [47] countries, indicating a large population potentially at risk. Accurate assessment of the risk posed by ZIKV infection to pregnant women and their babies in both Africa and southeast Asia should be a priority.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of thorough surveillance, together with myriad co-circulating pathogens causing febrile illnesses, make understanding both the past and current prevalence of gestational ZIKV infection and any resulting fetal outcomes in Africa challenging [4042]. Recent seroprevalence studies have now identified low, but consistent circulation of ZIKV in several African [4346] and southeast Asian [47] countries, indicating a large population potentially at risk. Accurate assessment of the risk posed by ZIKV infection to pregnant women and their babies in both Africa and southeast Asia should be a priority.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we recently reported that ZIKV infection is relatively common in HIV-infected persons in Ghana, and we will seek to further describe these interactions in places where coinfection might exist. [ 18 ] We will also explore specific mechanisms of hepatocyte injury due to Zika infection in subsequent work.…”
Section: Discussionmentioning
confidence: 99%
“…SIV-induced disease in macaques manifests similarly to HIV-induced disease in humans, making SIV-infected macaques a useful model for the study of human HIV infection 20 . Areas of high HIV prevalence in sub-Saharan Africa also overlap with areas of historical ZIKV infections [21][22][23] . Additionally, African-lineage ZIKV strains show greater pathogenicity in mice than Asian-lineage strains and resulted in resorption of all embryos in dams infected with African-lineage ZIKV 24,25 .…”
Section: Body Textmentioning
confidence: 99%